TIPIKALIS MOTIF KUPU-KUPU DARI SUKU ENGGROS PAPUA - nathalia dwijayanti nathalia (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2019)
Batik is a cultural heritage of ancestors which is still developing. Batik in Indonesia has its own diversity and distinctive characteristics, including in the Papua region. In Papua batik has characteristics that describe animals, plants and musical instruments. In this study, the use of motifs in Enggros tribe has a different position from each of its clans. Some motifs in the Enggros cannot be used by other clans. Each of these batik motifs has a meaning and hereditary meaning. This study uses a review of the shape of the motif, colour, and aesthetic value. The research method uses a qualitative descriptive method supported by the hermeneutic theory as a method of obtaining a valid interpretation of objectivity. The results of this research discussion reveal about Enggros batik as a characteristic of the Enggros tribe whose surname is from the Iwo Tribe. Expectations achieved in this study can help and find out the motives of the Enggros and the community is expected to understand more deeply these motifs as a legacy of ancestral tradition.